Inovasi Mesin Peluruh Biji Jagung sebagai Teknologi Tepat Guna Pascapanen di Desa Watugong untuk Mendukung Pertanian Berkelanjutan - Servianus, Yohanes; Baha, Abraham D.; Leta, Emanuel; F. X Wara Wangge, Gusti; Pereira Maia Pinto, Gaspar (Blueprint Journal, 2025)
Watugong Village, located in Alok Timur District, Sikka Regency, is a traditional agricultural area where maize serves as both a staple crop and an integral part of local cultural heritage. However, post-harvest processing—particularly the shelling of maize kernels from the cob—is still conducted manually, leading to inefficiency and reduced grain quality. Attempts at mechanization through modern machines have often proven unsuitable due to their high cost, complexity, and incompatibility with the needs of small-scale farmers. To address this issue, the Mechanical Engineering Department of Politeknik Cristo Re developed a 20 kg-capacity maize shelling machine that is ergonomic, affordable, and easy to operate. Powered by a 0.75 kW electric motor, the machine employs a transmission system comprising pulleys, V-belts, and a silent chain, enabling it to increase shelling efficiency by more than 4.5 times compared to manual methods. Performance tests show a shelling capacity of up to 400 kg/hour with minimal kernel damage. The novelty of this machine lies in its participatory design approach and use of locally available materials and components. This innovation serves as a tangible example of appropriate technology grounded in local wisdom, supporting improved productivity, farmer self-reliance, and sustainable food security in rural communities.